Determining the Critical Success Factors of the Wine Tourism Region of Napa from a Supply Perspective. (19th December 2013) - Jones, Marjorie F.; Singh, Neha; Hsiung, Yvonne
Abstract Napa is a renowned region for wine tourism and demonstrates how wine can be an instrument to develop tourism. The purpose of this research is to identify the critical success factors that have shaped the area's rise and growth, and its unique competitiveness in both the domestic and global marketplaces for wine tourism destinations. The findings from the research provide the foundation for a proposed conceptual model of success factors in wine tourism research and as insight to practitioners/suppliers. Findings reveal an aligned marketing effort and strategic partnerships among suppliers of Napa wine tourism. Copyright © 2013 John Wiley & Sons, Ltd.